2013
DOI: 10.1515/hf-2013-0077
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of drying of Masson pine lumber and its asymmetrical moisture content profile

Abstract: A mathematical model is discussed in terms of moisture transfer during the drying process of Masson pine (Pinus massoniana) lumber in industrial practice. The model was validated by comparing the simulated result of moisture distribution with experimental data. In the model, the wood drying process was divided into two phases. The first one dealt with processes above fiber saturation point (FSP), that was driven by capillary flux of free water and conductive flux of vapor, and the second one dealt with those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…En particular, en el secado de madera, se emplean modelos matemáticos que se encargan de describir adecuadamente fenómenos de transporte de calor y masa basado en sistemas de ecuaciones diferenciales. Dichos modelos pueden ser agrupados en tres tipos: modelos fenomenológicos (Salinas et al 2008), según enfoque de Luikov (1966) y multi-fásicos (Whittaker 1977), una revisión de este tema es dada por (Zhang et al 2014). Particularmente relevante resultan los trabajos que incorporan etapas de secado ampliamente documentadas en la literatura relacionadas con el contenido de humedad crítico (CHC) y el punto de saturación de la fibra (PSF) (Derdour et al 2007 andZhao et al 2016).…”
Section: Introductionunclassified
“…En particular, en el secado de madera, se emplean modelos matemáticos que se encargan de describir adecuadamente fenómenos de transporte de calor y masa basado en sistemas de ecuaciones diferenciales. Dichos modelos pueden ser agrupados en tres tipos: modelos fenomenológicos (Salinas et al 2008), según enfoque de Luikov (1966) y multi-fásicos (Whittaker 1977), una revisión de este tema es dada por (Zhang et al 2014). Particularmente relevante resultan los trabajos que incorporan etapas de secado ampliamente documentadas en la literatura relacionadas con el contenido de humedad crítico (CHC) y el punto de saturación de la fibra (PSF) (Derdour et al 2007 andZhao et al 2016).…”
Section: Introductionunclassified
“…Luikov (1966Luikov ( , 1975 developed a set of coupled partial differential equations for this purpose. The wood properties as a function of moisture content have to be considered in mathematical models (MacLean 1941;Siau 1983;Skaar 1988;Trcala 2012;Zhang et al 2014). Recent developments in this field confirmed that the experimental results and model predictions are in good agreement, while the thermo-physical properties of wood influence the accuracy (Kocaefe et al 2006;Younsi et al 2007Younsi et al , 2008Zhu and Kaliske 2011).…”
Section: Introductionmentioning
confidence: 99%